Assessing Clinical Competencies of Intern Nursing Students: AComparative Study in both Private and Governmental Health Sectors - El-Shrief, Hayam; Ageiz, Marwa (International Journal of Nursing Research, 2023)
Aim: This study aimed to assess the clinical competence of nursing intern students in both private and governmental health sectors and then to compare the clinical competency of intern students in both sectors. Subjects and Methods: Descriptive cross-sectional comparative research design was used. This study was conducted at two health sectors in Egypt, including governmental sectors (Teaching Hospital and Menoufia University Hospital in Shebin El-Kom, Menoufia Governorate, and Naser Institute) and private sector (El-Salam International Hospital, International Medical Center, and Omoma Hospital). The participants of this study included all intern students (n = 105) enrolled in the internship program during the academic year 2017–2018 at the Faculty of Nursing, Menoufia University. Tool: First tool: Self-Assessment Clinical Competence Questionnaire was used to conduct this study. Second Tool: Clinical competence questionnaire was used as an observational checklist to observe the actual clinical competence level of the intern students. Result: The highest percentage of the studied sample achieved an excellent level of competence at both hospitals regarding all competency domains. However, the general performance domain of competency had the highest score. Conclusions: There were statistically significant differences between both hospitals (governmental and private) regarding all competency domains, as the majority of intern students at the private hospitals achieved an expert competence level than intern students at the governmental hospitals.